Evaluating the performance of triple and double metal gate charge plasma transistors for applications in biological sensors at a dual cavity location - Akanksha Singh; Rajendra Kumar (Measurement: Sensors)
Background: Biosensors have become essential tools in biotechnology, environmental monitoring, and healthcare industries due to their ability to detect and analyze biological signals. However, conventional Tunnel Field-Effect Transistors (TFETs) used in biosensors face challenges like reduced ON-state current, random dopant fluctuations, and complex manufacturing processes, which limit their effectiveness. Aim: The study aims to investigate the effectiveness of Charge Plasma-based Tunnel Field-Effect Transistors (CP-TFETs) with dual and triple metal gate-dual cavity locations for improving the sensitivity and performance of biosensors. Methodology: The study compares dual and triple metal gate CP-TFET configurations for signal amplification and detection in biosensors. The CP-TFETs use high-k gate dielectric materials to enhance ON-state current and reduce OFF-state current, while the impact of neutralized and charged substances in the cavities on surface energy, electric field, and energy bands is analyzed. Results: The triple metal gate configuration demonstrated superior sensitivity in detecting biomolecules compared to the dual metal gate. By utilizing high-k materials and optimizing the gate work function, the triple metal gate approach achieved higher drain current and reduced OFF-state current, leading to improved overall performance. Conclusion: The triple metal gate CP-TFET outperforms its dual metal counterpart in biosensor applications, offering higher sensitivity, increased ON-state current, and improved detection capabilities, making it a promising approach for enhancing biosensor effectiveness.